Screening and identification of 3‐aryl‐quinolin‐2‐one derivatives as antiviral agents against influenza A. Issue 1 (5th December 2022) - Cheng, Huimin; Fu, Liangbing; Yang, Xia; Yang, Yujian; Zhang, Zhening; Tao, Yuan; Wan, Junting; Tu, Zhengchao; Chen, Jianxin; Li, Yingjun
Abstract: Quinolin‐2‐one represents an important and valuable chemical motif that possesses a wide variety of biological activities; however, the anti‐influenza activities of quinolin‐2‐one‐containing compounds were rarely reported. Herein, we describe the screening and identification of 3‐aryl‐quinolin‐2‐one derivatives as a novel class of antiviral agents. The 3‐aryl‐quinolinone derivatives were synthesized via an efficient copper‐catalyzed reaction cascade that we previously developed. Using this synthetic method, preliminary structure–activity relationships of this scaffold against the influenza A virus infection were systematically explored. The most potent compound 34 displayed IC50 values of 2.14 and 4.88 μM against the replication of H3N2 (A/HK/8/68) and H1N1 (A/WSN/33) strains, respectively, without apparent cytotoxicity on MDCK cells. We further demonstrated that 27 and 34 potently inhibited the plaque formation of the IAV, rendering this scaffold attractive for pursuing novel anti‐influenza agents.